Air pollution impacts on in-hospital case-fatality rate of ischemic stroke patients - Keller, Karsten; Haghi, Seyed Hamed Rastguye; Hahad, Omar; Schmidtmann, Irene; Chowdhury, Sourangsu; Lelieveld, Jos; Münzel, Thomas; Hobohm, Lukas (Thrombosis research, 2023)
Background - A growing body of evidence suggests that air pollution exposure is associated with an increased risk for cardiovascular diseases. Data regarding the impact of long-term air pollution exposure on ischemic stroke mortality are sparse. - Methods - The German nationwide inpatient sample was used to analyse all cases of hospitalized patients with ischemic stroke in Germany 2015-2019, which were stratified according to their residency. Data of the German Federal Environmental Agency regarding average values of air pollutants were assessed from 2015 to 2019 at district-level. Data were combined and the impact of different air pollution parameters on in-hospital case-fatality was analyzed. - Results - Overall, 1,505,496 hospitalizations of patients with ischemic stroke (47.7% females; 67.4 % ≥70 years old) were counted in Germany 2015-2019, of whom 8.2 % died during hospitalization. When comparing patients with residency in federal districts with high vs. low long-term air pollution, enhanced levels of benzene (OR 1.082 [95%CI 1.034-1.132],P = 0.001), ozone (O3, OR 1.123 [95%CI 1.070-1.178],P < 0.001), nitric oxide (NO, OR 1.076 [95%CI 1.027-1.127],P = 0.002) and PM2.5 fine particulate matter concentrations (OR 1.126 [95%CI 1.074-1.180],P < 0.001) were significantly associated with increased case-fatality independent from age, sex, cardiovascular risk-factors, comorbidities, and revascularization treatments. Conversely, enhanced carbon monoxide, nitrogen dioxide, PM10, and sulphur dioxide (SO2) concentrations were not significantly associated with stroke mortality. However, SO2−concentrations were significantly associated with stroke-case-fatality rate of >8 % independent of residence area-type and area use (OR 1.518 [95%CI 1.012-2.278],P = 0.044). - Conclusion - Elevated long-term air pollution levels in residential areas in Germany, notably of benzene, O3, NO, SO2, and PM2.5, were associated with increased stroke mortality of patients. - Research in context - Evidence before this study: Besides typical, established risk factors, increasing evidence suggests that air pollution is an important and growing risk factor for stroke events, estimated to be responsible for approximately 14 % of all stroke-associated deaths. However, real-world data regarding the impact of long-term exposure to air pollution on stroke mortality are sparse. Added value of this study: The present study demonstrates that the long-term exposure to the air pollutants benzene, O3, NO, SO2 and PM2.5 are independently associated with increased case-fatality of hospitalized patients with ischemic stroke in Germany. Implications of all the available evidence: The results of our study support the urgent need to reduce the exposure to air pollution by tightening emission controls to reduce the stroke burden and stroke mortality.